2016
DOI: 10.1152/ajpendo.00270.2016
|View full text |Cite
|
Sign up to set email alerts
|

Physiological processes underlying organ injury in alcohol abuse

Abstract: This review summarizes the American Physiological Society (APS) Presidential Symposium 1 entitled "Physiological Processes Underlying Organ Injury in Alcohol Abuse" at the 2016 Experimental Biology meeting. The symposium was organized by Dr. Patricia Molina, past president of the APS, was held on April 3 at the Convention Center in San Diego, CA, and was funded by the National Institute on Alcohol Abuse and Alcoholism. The "Physiological Processes Underlying Organ Injury in Alcohol Abuse Symposium" assembled e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 94 publications
(128 reference statements)
0
20
0
5
Order By: Relevance
“…In keeping with this notion, preliminary studies suggested diminished ethanol-induced anxiety in inhibitor-treated mice compared with untreated animals as evaluated by the open field test (Hsu and Haj, data not shown). Systemic delivery of PTP1B inhibitor may be of value as alcohol can permeate a plethora of tissues with adverse consequences [ 71 ]. Indeed, PTP1B inhibition using antisense oligonucleotides enhances insulin sensitivity and decreases weight in T2D patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with this notion, preliminary studies suggested diminished ethanol-induced anxiety in inhibitor-treated mice compared with untreated animals as evaluated by the open field test (Hsu and Haj, data not shown). Systemic delivery of PTP1B inhibitor may be of value as alcohol can permeate a plethora of tissues with adverse consequences [ 71 ]. Indeed, PTP1B inhibition using antisense oligonucleotides enhances insulin sensitivity and decreases weight in T2D patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…No Brasil, o consumo de bebidas alcoólicas é observado em 50% da população adulta [51]. O seu uso é associado à presença de modificações fisiológicas consideráveis e pode gerar efeitos prejudiciais em diferentes sistemas no organismo [52]. Estudos demonstram que a ingestão de álcool em concentrações de 4%, 10% e 40% (v/v) é responsável pelo retardo do esvaziamento gástrico e da redução da motilidade intestinal [53,54].…”
Section: Alcoolismounclassified
“…Estudos demonstram que a ingestão de álcool em concentrações de 4%, 10% e 40% (v/v) é responsável pelo retardo do esvaziamento gástrico e da redução da motilidade intestinal [53,54]. O seu consumo é capaz também de gerar lesões nas células hepáticas e alterar as enzimas metabólicas presentes no fígado [52].…”
Section: Alcoolismounclassified
“…Alcohol use disorder is a major health issue with enormous socioeconomic costs. The detrimental effects of acute and chronic alcohol consumption on liver, pancreas, and brain are well documented 1 . Chronic alcohol consumption also causes the loss of skeletal muscle strength and cardiac contractile function 2,3 .…”
Section: Introductionmentioning
confidence: 99%